Zakat Management in Countries that Require Zakat and Countries That Do Not Require Zakat - Djafar; Mukhtar Lutfi; Rahmawati Muin; Sugianto (Formosa Journal of Sustainable Research, 2023)
Zakat is an obligation for every individual who is Muslim, zakat is imposed when it has reached the nisab and haul, in this paper the author conveys that there are several countries in the world that impose mandatory zakat in these countries and countries that do not require zakat for their citizens who are Muslim but leave it to the Muslims themselves. The author uses a descriptive research method in the form of library research (library research). The results of the study show that in the management of zakat there are countries that intervene directly in the collection and distribution of zakat in these countries, including Saudi Arabia, Jordan, Pakistan, Sudan, Malaysia and Brunei, there are also countries that do not intervene but these countries provide space for their citizens to conducting zakat collection activities, these countries include Egypt, Kuwait, Turkey, and Indonesia. In line with this, the zakat management model carried out by each country depends on the conditions and political situation of the country so that various patterns of zakat collection are born. in real terms, if the management of zakat is properly accommodated, it will become a new economic power in a country and this will of course help the country in improving the standard of living of its people because life is mutually supportive and mutual cooperation in the zakat management system